Complications of invasive mechanical ventilation in critically Ill Covid-19 patients - A narrative review. (August 2022) - Khan, Wajiha; Safi, Adnan; Muneeb, Muhammad; Mooghal, Mehwish; Aftab, Ali; Ahmed, Jawad
Abstract: Critically ill COVID-19 patients have to undergo positive pressure ventilation, a non-physiological and invasive intervention that can be lifesaving in severe ARDS. Similar to any other intervention, it has its pros and cons. Despite following Lung Protective Ventilation (LPV), some of the complications are frequently reported in these critically ill patients and significantly impact overall mortality. The complications related to invasive mechanical ventilation (IMV) in critically ill COVID-19 patients can be broadly divided into pulmonary and non-pulmonary. Among pulmonary complications, the most frequent is ventilator-associated pneumonia. Others are barotrauma, including subcutaneous emphysema, pneumomediastinum, pneumothorax, bullous lesions, cardiopulmonary effects of right ventricular dysfunction, and pulmonary complications mimicking cardiac failure, including pulmonary edema. Tracheal complications, including full-thickness tracheal lesions (FTTLs) and tracheoesophageal fistulas (TEFs) are serious but rare complications. Non-Pulmonary complications include neurological, nephrological, ocular, and oral complications. Highlights: The complications related to IMV in critically ill covid 19 patients can be broadly divided into pulmonary and non-pulmonary complications. Among pulmonary complications the most frequent is Ventilator associated pneumonia. Others are Barotrauma, Cardiopulmonary effects of right ventricular dysfunction & Pulmonary complications mimicking cardiac failure including pulmonary edema, tracheal complications including full thickness tracheal lesions & tracheoesophageal fistulas. Non-Pulmonary complications of prolonged IMV include neurological, nephrological, ocular and oral complications.